2014
DOI: 10.1108/jpbm-02-2014-0499
|View full text |Cite
|
Sign up to set email alerts
|

A semiotic analysis of the extendibility of luxury brands

Abstract: Purpose – Considering a long-term perspective and the discourse directly emitted by brands, the aim is to study how can brand extension potential be predicted through the analysis of brand contracts? Design/methodology/approach – Considering a long-term perspective and the discourse directly emitted by brands, the aim is to study how can brand extension potential be predicted through the analysis of brand contracts? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
0
21
0
6
Order By: Relevance
“…Sood and Keller () stated that branding strategies deserve greater attention in the study of parent brand spillover effects. In a study on extendibility of luxury brands, Veg‐Sala and Roux () reported in their research implications that, because of the potential damage an extension can cause to a luxury brand, the latter could develop a branding strategy by creating an independent/standalone brand, a sub‐brand, or an umbrella brand. The current study intends to close this gap in the literature, since the effect of branding strategy will be tested at varying levels for each type of extension.…”
Section: Research Background and Hypothesis Developmentmentioning
confidence: 99%
“…Sood and Keller () stated that branding strategies deserve greater attention in the study of parent brand spillover effects. In a study on extendibility of luxury brands, Veg‐Sala and Roux () reported in their research implications that, because of the potential damage an extension can cause to a luxury brand, the latter could develop a branding strategy by creating an independent/standalone brand, a sub‐brand, or an umbrella brand. The current study intends to close this gap in the literature, since the effect of branding strategy will be tested at varying levels for each type of extension.…”
Section: Research Background and Hypothesis Developmentmentioning
confidence: 99%
“…Moreover, these articles use only consumer perceptions to analyse the success or failure of cross-gender extensions (Jung and Lee, 2006;Ulrich, 2013). But it has been shown that another approach can be used, based on the discourses directly produced by brands (Veg-Sala and Roux, 2014). This approach allows us to define brand extension potential (BEP) and has been especially developed for luxury brands.…”
Section: Brand Gender and Cross-gender Extensionmentioning
confidence: 99%
“…Beyond this approach focused on consumer evaluations, the definition of brand extension potential (BEP) reflects a long-term approach to brand management. Brand extension potential defines how far a brand can be extended consistently and legitimately according to what it is (Veg-Sala and Roux, 2014). The BEP concept does not focus on consumer perceptions but on a more managerial approach based on the study of brand identity (Kapferer, 2004).…”
Section: Brand Extension Potential (Bep) Of Luxury Brandsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, innovation kills tradition. In contrast, marketing can use tradition in the form of brand identity as a validation criterion for evaluating new designs proposed by designers (Spiggle, Nguyen, & Caravella, 2012; Veg‐Sala & Roux, 2014). Thus, marketing may be tempted to reject innovative designs as they constitute a threat to brand tradition.…”
Section: Introductionmentioning
confidence: 99%